Enabling structural resilience of street-involved children and youth in Kenya: reintegration outcomes and the Flourishing Community model - Goodman, Michael L.; Seidel, Sarah E.; Springer, Andrew; Elliott, Aleisha; Markham, Christine; Serag, Hani; Keiser, Philip; Raimer, Ben; Raimer-Goodman, Lauren; Gatwiri, Christine; Munene, Kelvin; Gitari, Stanley (Frontiers in Psychology, 2023)
Acknowledgements: We are deeply indebted to the millions of children and youth living in streetsituations globally, and most particularly the young people we are fortunate to work with towards a better world. Your tenacity, grit, and resolve humble us, and fortify our efforts to create the conditions where you can become all you are able to become. We are equally grateful to families and communities active in Sodzo Kenya programming, helping us to learn how you flourish and what we may do to support your doing so. To the government, faith, non-government, traditional and community leaders and partners who make this work possible within Kenya -we are forever in your service.